Development of Mathematics Learning e-Modules to Improve Students' Mathematical Communication Skills - Kasih, Aminah Cinda; Siregar, Tanti Jumaisyaroh (International Journal of Trends in Mathematics Education Research, 2024)
E-modules can be used as a self-paced learning process that can help students learn systematically, interestingly, and interactively. The teaching and learning process is also not limited to an information source, this e-module can help students understand concepts better than the material taught by relevant teachers. This research uses research and development (Research and Development) is a research method used to produce certain products and test the effectiveness of products with a 4D model. The subject of this study is grades VII students at MTs. Amin Darussalam. It consists of one class that is randomly selected (random sampling), namely class VII as many as 6 students who are made into a limited field test or a small test group consisting of 20 students and an operational field test or a large test. The feasibility level of the e-module obtained a feasibility level of 81.83%, with a very feasible category. The assessment of the validity level is 81.47% with a category that is quite valid, can be used but needs minor revisions. The assessment of the practicality level is 73.25% with the practical category. The assessment of the effectiveness level of the e-module is 0.84 with the effective category.